Hand recognition solution as conference room intelligent lighting control technique - BÖCEKÇİ, VEYSEL GÖKHAN; KIYAK, İSMAİL (My University, 2023)
In communication technologies, it can be solved in systems that are extremely simple, detailed, among the tools for use in the electronic environment, internet-connected, development and integrated systems. With the rapid development of technology, smart led lamps, smart office, smart conference room lighting, road lighting fixtures and therefore smart lighting systems have been the reason why smart lighting systems can enter daily life rapidly. Sensors which are the components of smart lighting systems, feedback from users, cloud services, smart algorithms become more widespread with artificial intelligence in an easier, faster, and more economical way, causing a change in traditional lighting control and improvements in energy saving, functionality, and user centered lighting. In this study, the mediapipe framework is intended to be used for office conference room. MediaPipe is indeed an open-source framework that enables the processing of computer vision data, including video and audio. The lighting system was built using the artificial intelligence supported mediapipe hand recognition solution, and artificial intelligence and image processing algorithms were used. Each hand gesture corresponds to a different command to control the light. There are 3 main menus are determined for the hand and defined to the system. Main menus can be reached with every hand movement. After entering the main menu, intermediate menus are processed. Lighting application can be realized through control commands obtained by hand movements, digital/analog information conversion and Dali control system. It is concluded that the ease of control brought by this method is more advantageous in terms of its purpose than other methods because it is contactless and does not require any hardware device in the hands of the presenter.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Bilgisayar Bilimleri; Algoritmalar; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Computer Sciences; algorithms; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; ENGINEERING; AUTOMATION & CONTROL SYSTEMS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; ENGINEERING, MANUFACTURING; Yapay Zeka; Fizik Bilimleri; Bilgisayar Bilimi Uygulamaları; Bilgisayarla Görme ve Örüntü Tanıma; Endüstri ve İmalat Mühendisliği; Kontrol ve Optimizasyon; Artificial Intelligence; Physical Sciences; Computer Science Applications; Computer Vision and Pattern Recognition; Industrial and Manufacturing Engineering; Control and Optimization; artificial intelligence; image processing; lighting control; mediapipe; smart lighting